Differentiation of Osteophytes and Disc Herniations in Spinal Radiculopathy Using Susceptibility-Weighted Magnetic Resonance Imaging. Issue 2 (February 2017) - Bender, Yvonne Yi-Na; Diederichs, Gerd; Walter, Thula Cannon; Wagner, Moritz; Liebig, Thomas; Rickert, Marcus; Hermann, Kay-Geert; Hamm, Bernd; Makowski, Marcus Richard
Abstract : Objective: The aim of this study was to evaluate the diagnostic performance of susceptibility-weighted magnetic resonance imaging (SW-MRI) for the differentiation of osteophytes and disc herniations of the spine compared with that of conventional spine MR sequences and radiography. Materials and Methods: This study was approved by the local ethics review board; written consent was obtained from all subjects. Eighty-one patients with suspected radiculopathy of the spine were included prospectively. Radiography, T1/T2, and SW-MRI of the cervical/lumbar spine were performed. As reference standard, 93 osteophytes (n = 48 patients) were identified on radiographs in combination with conventional T1/T2 images. One hundred fourteen posterior disc herniations (n = 60 patients) were identified on T1/T2 in combination with radiography excluding osteophytes. For this study, 2 observers independently assessed the presence of osteophytes and disc herniations on T1/T2 and SW-MRI, with radiographs excluded from the analysis. In a subgroup of patients (n = 19), additional computed tomography images were evaluated. Sensitivity, specificity, and interobserver agreement were calculated. Results: Most osteophytes (n = 92 of 93) and disc herniations (n = 113 of 114) could be identified and differentiated on SW-MRI magnitude/phase images, if radiographs were excluded from analysis. Susceptibility-weighted magnetic resonance imaging achieved a sensitivity of 98.9% and specificity of 99.1% for the identification of osteophytes. Conventional T1/T2 spine MR sequences achieved a sensitivity and specificity of 68.6% and 86.5%, respectively, if radiographs were excluded from analysis. Regarding the size of osteophytes, SW-MRI showed a strong correlation with computed tomography ( R 2 = 0.96) and radiography ( R 2 = 0.95). In addition, SW-MRI achieved a higher interobserver agreement compared with conventional MR. Conclusions: Susceptibility-weighted magnetic resonance imaging enables the reliable differentiation of osteophytes and disc herniations in patients with spinal radiculopathy with a higher sensitivity and specificity compared with conventional T1/T2 MR sequences.